From activity to learning: using cultural historical activity theory to model school library programmes and practices - E.M. Meyers (Information Research: An International Electronic Journal)
Introduction. changes in educational policy and practice demand that we examine school library programmes from a new perspective. As a model that takes a developmental view of minds in context, Cultural Historical Activity Theory is particularly well suited to the study of school libraries and the learning that occurs therein. This paper focuses on the activity theoretic concepts of 'contradictions' and 'expansive learning' as they relate to the development of best practices. Method. Developmental Work Research was applied as a guiding methodology in an intervention study of six high school libraries in Washington State, USA. Library activity is illustrated from multiple perspectives using a triangulated, qualitative approach. Analysis. contradictions and tensions in the general school library activity system are identified, and an intervention was designed to facilitiate the development of expansive instruments. A case example illustrates a second level of analysis and specific points of intervention. Results. analysis reveals that the tensions and contradictions provide opportunities for expansive learning on the part of the teacher-Librarians. The research team can use practitioners' zones of proximal development to guide the alignment of library programme goals and practices. Conclusion. : some limitations and future promise of the framework and its application are discussed. The proposed activity theory toolkit suggest a new way of exploring the practices of teacher-librarians, incorporating research evidence, professional expertise, and reflective decision making.